Absolute and relative strength, power and physiological characteristics of Indian junior national-level judokas - Harris, D. M.; Kendall, K.; Haff, G. G.; Latella, C. (Sports, 2020)
The physical qualities that underpin successful junior judokas requires continuing investigation. We investigated the physical and physiological characteristics of junior national level judokas. We tested 25 (15 male, 10 female) Indian judokas for absolute and relative strength (back-squat and bench-press one-repetition maximum (1RM) as well as isometric handgrip), aerobic (RAMP test) and lower-body anaerobic power (Wingate 6-s sprint and countermovement jump), change-of-direction (5-0-5 test) and speed (30 m sprint). Athletes were grouped according to national-level competition placing (gold-medal winners (GM; n = 8), all medal winners (MW; n = 13), non-medallists (NM; n = 12), and NM plus silver and bronze; all others (AO; n = 17)). Stepwise discriminant function analysis determined characteristics likely to predict successful performance. Independent t-tests and effect size (Hedge`s g) analyses were performed between groups. GM demonstrated greater lower-body absolute (20.0%; g = 0.87, p = 0.046) and relative 1RM strength (21.0%; g = 0.87, p = 0.047), and greater lower-body absolute (25.4%; g=1.32, p=0.004) and relative (27.3%; g = 1.27, p = 0.005) anaerobic power compared to AO. Furthermore, anaerobic power can correctly predict 76.5% and 62.5% of AO and GM athletes, respectively. No differences were observed between MW and NM groups. The results suggest the importance of lower-body strength and power for junior national-level judokas and provides information for professionals working with these athletes.